Structural, electronic, magnetic and elastic properties of xenon-based fluoroperovskites XeMF3 (M = Ti, V, Zr, Nb) via DFT studies. Issue 42 (28th September 2022) - Abdullah,; Sajjad, Muhammad; Khan, Umar Ayaz; Ullah, Hamid; Alhodaib, Aiyeshah; Amami, Mongi; Tirth, Vineet; Zaman, Abid; Shazia,
Abstract : In this work, the structural, electronic, magnetic and elastic properties of the xenon-based fluoroperovskites XeMF3 (M = Ti, V, Zr, Nb) have been studied using density functional theory. Abstract : In this work, the structural, electronic, magnetic and elastic properties of the xenon-based fluoroperovskites XeMF3 (M = Ti, V, Zr, Nb) have been studied using density functional theory. The structural study reveals that all the perovskites have stable structures. A half-metallic nature is observed due to the presence of a band gap in only the spin-down channel. The result indicates that the considered compounds are ferromagnetic materials with integer magnetic moments. The elastic parameters were studied to obtain their elastic properties. It is noted that all compounds have an anisotropic nature and show ductility. The optical characteristics show that these compounds are good optical absorbers at high energy. Furthermore, we suggest that these compounds could be good candidates for spintronic and optoelectronic devices.